Development and initial psychometric testing of the Intrahospital Transport Safety Scale in intensive care - Lina Bergman; Wendy Chaboyer; Monica Pettersson; Mona Ringdal (BMJ Open)
Objective To develop and evaluate the psychometric properties of a scale measuring patient safety during the intrahospital transport process for intensive care.Design The scale was developed based on a theoretical model of the work system and patient safety, and items generated from participant observations. A Delphi study with international experts was used to establish content validity. Next, a cross-sectional study was undertaken to inform item reduction and evaluate construct validity and internal consistency.Setting The questionnaire was distributed to healthcare practitioners at 12 intensive care units in Sweden.Participants A total of 315 questionnaires were completed. Eligible participants were healthcare practitioners in the included units that performed an intrahospital transport during the study period. Inclusion criteria were (1) transports of patients within the hospital to undergo an examination or intervention, and (2) transports performed by staff from the intensive care unit. We excluded transports to a step-down unit or hospital ward.Outcome measures Psychometric evaluation, including item analysis, validity and reliability testing.Results Items were reduced from 55 to 24, informed by distributional statistics, initial reliabilities, factor loadings and communalities. The final factor model consisted of five factors, accounting for 59% of variance. All items loaded significantly on only one factor (>0.35). The original conceptual model of teamwork, transport-related tasks, tools and technologies, environment, and organisation was maintained with regrouping of items. Cronbach’s alpha ranged from 0.72 to 0.82 for each subscale (ie, factor).Conclusions The present study provides a self-report questionnaire to assess patient safety during intrahospital transport of patients in intensive care. The results indicate acceptable validity and reliability of the scale among a sample of Swedish healthcare practitioners. If further confirmatory testing supports the present results, this scale could be a useful tool to better understand safety prerequisites and improve clinical practice.